Utilization Assessment of Basic Maternity Health Services Through Mamta Card in Rural Ahmedabad - Govani, Kapil J; Sheth, Jay K; Bala, D V (National Journal of Community Medicine, 2013)
Introduction: Mamta card is a comprehensive MCH card as it provides the information of pregnant / lactating women and 0-3 years of Children. Objectives: To find the utilization of antenatal, Intranatal and postnatal health services by rural mothers and to assess completeness of records in the Mamta card. Methodology: Community based cross sectional study was conducted at nine villages of seven sub centres under two PHCs of rural Ahmedabad district during October-2011 to January-2012. Proforma was prepared covering various components of Mamta card. Total 130 mothers having infants (<1 year) were interviewed. Information was assessed primarily from the Mamta card or by directly asking the mother whenever the card was unavailable. Result: Out of total 130 mothers, 103 (79%) having mamta card. Majority (52%) were educated up to primary level. Documentation of treatment and advice was 82.5% for antenatal and only 3.9% for postnatal details. Date of birth was noted in 78.6%, birth weight in 67% and Growth chart mapping in 44.6% of mamta cards. Majority (76.9%) had taken at least 3 ANC visits. Around 95% mothers were fully immunized for TT, as per requirement. 52% mothers had taken IFA for at least 3 months. Majority (53%) delivered at private hospital. Beneficiaries of Janani-Suraksha Yojna were 32%. Preferable contraception was condom (16%) followed by Cu-T(7%), whereas majority(67%) were not using or did not reply. Conclusion: The coverage of basic maternity health services is unsatisfactory. Documentation was satisfactory only for antenatal details but not for rest of the services. Relevant steps are required to improve services and its documentation.